Estimation Some Heavy Elements in Drinking Water in Baghdad City / Al Rusafa - Salem Saleh Al-Tamimi (Journal of Global Pharma Technology, 2016)
This study aimed to identify the drinking water content of bacteria, yeast, mildew colon bacteria and heavy metals in Baghdad city /Al-Rusafa. Fifteen water samples were collected from different cities including (Al-Karrada, Al-Dora, Palestine street , Obeidi, Zafaraniyah, Kamaliyya, Zayouna, Adhamiya, Ur district, Talbiya, Jamila, Al-Bnouk district, Shaab, Baladiyat, Al- Mustansiriya district), Heavy elements were estimated in these samples, which including (Chrome Co, Lead pb, Copper CU, Cadmium Cd and Nickel Ni), Some microbiological tests were performed including detection of the total number of bacteria, Yeasts and Mildew and colon bacteria by using Bac Trac device. Results showed that heavy elements concentrations ranged from 0.1000-2.787 ppm for chrome element and 0.021-0.338 ppm for Lead, 0.0096-0.2461 ppm for copper, 0.2108-0.3308 ppm for Cadmium, and 0.0065-0.6556 ppm for Nickel. Clearly it was shown that concentrations of lead, chrome and cadmium higher than the Iraqi standard specifications specified No. 417 on 2009 related with drinking water. The results of this study showed that all samples were free from all microbial content and this result were matching by the Iraqi standard specifications above mentioned.Keywords: Iraqi drinking water-Microbial content-heavy metal.